A winning strategy for the Dama game - Delfino, Annalou B. (2002)
The dama game was properly defined by its given rule. A mathematical representation to the problem was obtained. The game tree of dama consists of two nodes namely the MAX and the MIN nodes. Each node represents the status of the game based on the rule of the game. The tree was subdivided into levels where the first level is called the MAX level; the second level is the MIN level and so on. The sixth level of the game tree was considered as the terminal level and the nodes are also the terminal node since the number of nodes at the next level is no longer manageable. An evaluation function then was used to evaluate each terminal node at the level six. Status labeling procedure was employed then to evaluate the ancestor nodes. This procedure determines the winning path of the game. Results showed that in a 4 x 4 dama game tree, the first player has high chance of winning the game. Optimality however cannot be identified for large game trees